Association between dietary zinc intake and abdominal aortic calcification in US adults. Issue 7 (11th July 2019) - Chen, Wei; Eisenberg, Ruth; Mowrey, Wenzhu B; Wylie-Rosett, Judith; Abramowitz, Matthew K; Bushinsky, David A; Melamed, Michal L
Abstract: Background: In animal studies, zinc supplementation inhibited phosphate-induced arterial calcification. We tested the hypothesis that higher intake of dietary zinc was associated with lower abdominal aortic calcification (AAC) among adults in the USA. We also explored the associations of AAC with supplemental zinc intake, total zinc intake and serum zinc level. Methods: We performed cross-sectional analyses of 2535 participants from the National Health and Nutrition Examination Survey 2013–14. Dietary and supplemental zinc intakes were obtained from two 24-h dietary recall interviews. Total zinc intake was the sum of dietary and supplemental zinc. AAC was measured using dual-energy X-ray absorptiometry in adults ≥40 years of age and quantified using the Kauppila score system. AAC scores were categorized into three groups: no AAC (AAC = 0, reference group), mild–moderate (AAC >0–≤6) and severe AAC (AAC >6). Results: Dietary zinc intake (mean ± SE) was 10.5 ± 0.1 mg/day; 28% had AAC (20% mild–moderate and 8% severe), 17% had diabetes mellitus and 51% had hypertension. Higher intake of dietary zinc was associated with lower odds of having severe AAC. Per 1 mg/day higher intake of dietary zinc, the odds of having severe AAC were 8% lower [adjusted odds ratio 0.92 (95% confidence interval 0.86–0.98), P = 0.01] compared with those without AAC, after adjusting for demographics, comorbidities and laboratory measurements. Supplemental zinc intake, total zinc intake and serum zinc level were not associated with AAC. Conclusions: Higher intake of dietary zinc was independently associated with lower odds of having severe AAC among noninstitutionalized US adults.